Dental caries experience and periodontal status of handicapped institutionalised black high school pupils in Soshanguve, Pretoria - Gugushe, T S (The Journal of the Dental Association of South Africa = Die Tydskrif van die Tandheelkundige Vereniging van Suid-Afrika, 1991)
This study compares the oral health status, as reflected by caries experience and periodontal status, of 3 cohorts of institutionalised handicapped pupils. The 3 groups of impairments studied were physical, visual and aural disability. 267 institutionalised handicapped high school pupils were examined. 163 (61 per cent) were physically, 84 (31.5 per cent) visually, and 20 (7.5 per cent) aurally handicapped. 34 per cent of the study population was caries-free with a mean DMFT of 2.63. There was no statistically significant difference (p greater than 0.05) between the caries experience of the three handicapped groups. Similarly no significant difference (p greater than 0.05) was observed between males and females. More than half of the calculus accumulation occurred among the physically disabled. At the 90 per cent confidence interval there was no significant difference in bleeding and shallow pocketing among the three groups. However, there was a significant difference for the presence of calculus. The physically disabled pupils consistently indicated the highest proportion of bleeding, calculus accumulation and shallow pocketing.